The Estrogen Receptor Concentration and Col3A1 Gene Immunoexpression in Uterosacral Ligament is Correlated with Postmenopausal Uterine Prolapse - Erick C. Asmara (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To analyze correlation between concentration of estrogen receptor and imunoexpression of Col3A1 gene on uterosacral ligament of postmenopausal uterine prolapse patient. Methods: This is a cross-sectional analytic observational study involving 32 subjects who met inclusion criteria. Samples are taken consecutively in Dr. Hasan Sadikin Hospital in January 1st - December 31st 2012. Statistical analysis was performed with non-parametric Mann-Whitney test and Spearman’s rho non-parametric correlation test. Result: There is no significant difference of estrogen receptor concentration between postmenopausal women with and without uterine prolapse (p = 0.377), while there is no significant difference of Col3A1 gene immunoexpression between postmenopausal women with and without uterine prolapse (p = 0.119) either. There is a significant positive correlation between the estrogen receptor concentration and Col3A1 gene immunoexpression in uterosacral ligament of postmenopausal uterine prolapse patients (p = 0.002, r= 0.711). Conclusion: There is a positive correlation between the estrogen receptor concentration and Col3A1 gene immunoexpression in uterosacral ligament of postmenopausal uterine prolapse patients. [Indones J Obstet Gynecol 2013; 37-2: 103-6] Keywords: Col3A1 gene, estrogen receptor, menopause, uterine prolapse, uterosacral ligamen